Pelatihan Kahoot untuk Pembuatan Kuis Online bagi Guru TK Tarbiyatul Athfal Kaliaman 02, Kecamatan Kembang, Kabupaten Jepara - Ahmad Asroni (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
This article discusses the results of community service entitled kahoot training for making online quizzes for Tarbiyatul Athfal Kaliaman 02 Kindergarten teachers. The method used in this training is a combination of lecture, practice, and question-and-answer (Q&A) methods. The benefits of this training are: First, the existence of the kahoot makes learning activities more quality, interactive, and fun. Second, teachers gain a lot of knowledge, experience, and skills using the kahoot to create various educational and entertaining online quizzes. This skill was very useful, especially during the Covid-19 pandemic, learning at TK Tarbiyatul Athfal Kaliaman 02 was carried out online. Third, although during the Covid-19 pandemic, offline learning is rarely held, online quizzes using the kahoot really helps teachers in transferring knowledge to their students in a very fun way. Fourth, since using the kahoot tto create online quizzes, the lessons that teachers do are more varied, entertaining, and challenging. Students are also very happy with the online quizzes given by the teacher. Fifth, the kahoot attracts teachers and students because it is not paid (free of charge). Teachers and students only need to have a gadget in the form of a laptop, computer, or smart phone, to access and use the kahoot.